Development of a causal model of academic adjustment based on emotional self-regulation and orientation of tendency dominance and the mediating role of students\' academic flourishing - Soleiman Ashkoti; Bahman Kord; Hoshang Jadidi (مجله علوم روانشناختی, 2022)
Background: Academic Adjustment refers to the ability to adapt to new information, experiences, and learning environments. Among the important features that can affect academic adjustment is the ability of emotional self-regulation and orientation of tendency-dominance with the mediating role of academic flourishing in students. However, so far, no research has examined the integration of the relationships of these variables in the form of a comprehensive model. Aims: This study was conducted to develop a causal model of academic adjustment based on emotional self-regulation and orientation of tendency-dominance and the mediating role of academic flourishing in students. Methods: In this descriptive-correlational study, the statistical population included 384 people consisted of all high school second-grade students in Mahabad in 2019-2020, which were selected by multi-stage cluster sampling. Research instruments include the Achievement Goal Questionnaire (Elliott & Murayama) (AGQ-R), March's Emotional Self-Regulation Questionnaire (1998), the Diner and Biswas Academic Flourishing Scale (2008), and the Baker and Cyriac Standard Adjustment Questionnaire (1984). The evaluation of the proposed model was performed using the path analysis method. Results: The results showed that the variables of emotional self-regulation (P= 0.001), orientation of tendency-dominance (P= 0.004) and academic flourishing (P= 0.001) predicted academic adjustment directly. Also, emotional self-regulation (P= 0.001) and orientation of tendency-dominance (P= 0.001) have a direct relationship with academic flourishing. Emotional self-regulation and orientation of tendency-dominance have an indirect relationship with the mediation of academic flourishing on academic adjustment (P= 0.001). Conclusion: According to the findings of this study, academic flourishing (in the meaning of the desire to progress and get better) plays a significant mediating role in the relationship between emotional self-regulation, orientation of tendency- dominance and academic adjustment.